KERAGAMAN MAKROBENTHOS DI RAWA LEBAK PAMPANGAN KABUPATEN OGAN KOMERING ILIR PROVINSI SUMATERA SELATAN - Dina Muthmainnah (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
Macrobenthos are animals which live in bottom substrate of waters systems ie sand, mud, rock or rubble. This research aims to determine the macrobenthos diversity in three types of swamp in Pampangan ie floodplain swamp, rain-fed swamp and mix swamp. The research was conducted from October 2011 until March 2012 by collecting primary data and laboratorium analysis. The location of the research is lebak swamp, Pampangan subdistrict, Ogan Komering Ilir Regency, South Sumatra Province while identification of macrobenthos and sediment analysis at Research Institute for Inland Fisheries. The results show that there are 3 classes of macrobenthos, ie 9 species of Insecta, 1 species of Molusca and 11 species of Oligochaeta. Highest diversity index is in floodplain swamp while highest evenness index and species richness index are in the mix swamp. Similarity index of macrobenthos on the three types of swamp are low, it means that the animals come from different community. The differences of fertility level and texture of sediment will affect the diversity of macrobenthos.Â Key words: Diversity, macrobenthos, swamp, South Sumatra